Increasing the level of service through the implementation of 5S and MRP tools in SMEs marketing pharmaceutical products: An empirical investigation in Peru - Rodriguez Quispe, Angela Victoria (2022)
Nowadays, Peruvian SMEs, with an initial business model, seek and achieve good acceptance in the market, which are obliged to acquire the necessary knowledge and tools to be able to continue and manage a great change in the growth of the company. In this context, the research aims to implement the tools of industrial engineering in order to achieve the improvement in the level of service in a pharmaceutical SME. It was decided to perform an external analysis of the company to know the situation in which it is compared to others in the same sector and an internal analysis to determine its strengths and weaknesses. To identify the problem, a deeper analysis of the process will be carried out using the root-cause tree methodology, in which it is concluded that, due to poor management in the warehouse, there are delays in the attention of orders. For the implementation of the improvement, constructivism has been chosen as the theoretical framework, this choice is made with the purpose of knowing in depth the different theories that allow corroborating the benefits that the implementation of the different tools to be investigated have brought to the companies. In this case, the normative networks are studied in two ways, 5S and MRP tools. The methodology used for this purpose is based on a quantitative-descriptive analysis, which frames the registration, analysis and interpretation of an audit and checklist, as well as the times or processes of the phenomena that occur within the company. Finally, after implementing the 5S and MRP tools, the technical validations are carried out through audits and the Arena Simulation Software, respectively.